Optimization of Flooded Soil Recovery via Plant- Arbuscular Mycorrhizal Fungi Symbiotic Interaction - Nor Hazwani, Aziz; N., Zainol; Nanthinie, Thangaperumal; Nor Hanisah, Zahari (Bangladesh University of Engineering and Technology, 2017)
Flooded soil recovery was optimized using experimental design methodology by manipulating the symbiotic relationship between soil fungi, Arbuscular Mycorrhizal Fungi (AMF) and the host plant (Allium cepa L.) planted in a soil containing AMF (SA). This was achieved by measuring the amount of nutrient (nitrogen, phosphorus and potassium) uptake by AMF using HACH spectrophotometer after 14 days of planting in several condition suggested by Design-Expert® software (Ver 7.1.6). In order to determine the optimum condition for the AMF to recover the flooded soil, the experiments were designed according to a central composite design in two variables following the Response Surface Methodology (RSM). A quadratic polynomial model was generated to predict soil recovery. R2 for nitrogen, phosphorus and potassium was found at 0.89, 0.96 and 0.94 respectively of the range for the factors studied namely 24-32 ml water content and 4.0-6.0 cm depth of soil. Among two parameters, depth of soil showed significant effect on the recovery of flooded soil for phosphorus and potassium while for nitrogen both parameters showed insignificant effect. Model validation experiments showed good correspondence between experimental and predicted values at error for N, P, and K at 7.0%, 1.86% and 2.65% respectively. The optimal condition for soil recovery was at 28 ml soil water content and 5 cm soil depth. At this condition, the nutrient uptake by AMF was predicted to be at their maximum rate where the concentration of nutrients increased approximately by 2 to 3 times from the initial nutrient concentration.